Penentuan Jumlah Operator OPTIMAL dengan Metode Simulasi - Sudaningtyas, Satya (Jurnal Teknik Industri, 2012)
This study was conducted to apply simulation method on a service system in order to determine the numbers of optimum operator so that the performance of the system was better. The performance of system could be observed from various aspects. One of them was consumer waiting time. In this study, simulation was conducted on the existing service system and the proposed scenario service system. The result showed that the proposed scenario service system was succeed in decreasing consumer waiting time significantly at 14,75 minutes.Â